High-precision transition energy measurements of neon-like Fe xvii Ions - Shah, Chintan; Togawa, Moto; Botz, Marc; Danisch, Jonas; Goes, Joschka J.; Bernitt, Sonja; Maxton, Marleen; Köbnick, Kai; Buck, Jens; Seltmann, Jörn; Hoesch, Moritz; Gu, Ming Feng; et al. (The astrophysical journal, 2024)
We improve by a factor of 4-20 the energy accuracy of the strongest soft X-ray transitions of Fe xvii ions by resonantly exciting them in an electron beam ion trap with a monochromatic beam at the P04 beamline of the PETRA III synchrotron facility. By simultaneously tracking instantaneous photon-energy fluctuations with a high-resolution photoelectron spectrometer, we minimize systematic uncertainties down to 10-15 meV, or velocity equivalent ±∼5 km s−1 in their rest energies, substantially improving our knowledge of this key astrophysical ion. Our large-scale configuration-interaction computations include more than 4 million relativistic configurations and agree with the experiment at a level without precedent for a 10-electron system. Thereby, theoretical uncertainties for interelectronic correlations become far smaller than those of quantum electrodynamics (QED) corrections. The present QED benchmark strengthens our trust in future calculations of many other complex atomic ions of interest to astrophysics, plasma physics, and the development of optical clocks with highly charged ions.